Strategi Pengembangan Desa Wisata Berkelanjutan Menggunakan Analisis SWOT (Studi Kasus: Desa Tetebatu, Kecamatan Sikur, Lombok Timur) - Satriawan, Teguh (Politeknik Pariwisata Medan, 2024)
Tetebatu Tourism Village is the first and oldest tourism village in West Nusa Tenggara Province which has a variety of potential and tourist destinations ranging from natural, cultural and artificial tourism. Although it has many and varied tourism potentials and destinations, its development still cannot be fully developed properly and maximally. This study aims to determine the development strategy of Tetebatu Tourism Village so that it can continue to be sustainable based on SWOT analysis. The research method used in this research is a descriptive qualitative approach, the data collection techniques that researchers use are observation, interviews, and documentation. In determining the development strategy of Tetebatu Tourism Village, this research uses SWOT analysis. The results of this study indicate that the right strategy to be applied in the development of Tetebatu Tourism Village so that it can continue to be sustainable is to explore and maximize all tourism potential to increase the tourism attractiveness of Tetebatu Tourism Village, Increase cooperation with other tourism villages to create tour packages, Increase promotion through the media and cooperation with the Regional Government, Ministry, and other tourism villages, Improve and complete facilities and infrastructure to support tourism activities, Cooperate with the private sector, Maximize the management of tourist destinations through cooperation with the Regional Government and the Ministry to conduct training on tourism destination management, and Maximize all tourism potential and make new innovations to increase tourist attractiveness so as to be able to face competition with other tourist villages.